Black widow (2016), volume 1 ebook - Samnee, Chris (Black Widow (2016), 2018)
Wieder einmal holt die Vergangenheit Natasha Romanova ein, die als Black Widow einst zu den effizientesten Killern des KGB gehörte. Um zu verhindern, dass eine ihrer größten Sünden aus ihrem früheren Leben ans Licht kommt und ihr Verhältnis zu Tony Stark für immer vergiftet, würde Natasha alles tun. Auch die meist gesuchte Feindin von S.H.I.E.L.D. werden ... Author: Mark Waid & Chris Samnee. Illustrator: Chris Samnee. Copyright: © 2020 Marvel Characters, Inc. All rights reserved. All characters featured in this issue and the distinctive names and likenesses thereof, and all related indicia are trademarks of Marvel Characters, Inc. No similarity between any of the names, characters, persons, and/or institutions in this magazine with those of any living or dead person or institution is intended, and any such similarity which may exist is purely coincidental. www.marvel.com.com